Priority Development Areas in the Context of the Economic Security of Macro-Region - Chichkanov, Valery Petrovich; Belyaevskaya-Plotnik, Lyubov Aleksandrovna (Economy of Regions, 2018)
In March 2017, after the adoption of the Russian Federation Economic Security Strategy until 2030, the need for strengthening the security of the subjects of the Russian Federation including macro-regions became relevant. In this aspect, the Arctic zone of the Russian Federation deserves special attention as it is a strategically important not only for economic, but also the national security of the country. Therefore, at the present stage of the state development, the substantiation of the special measures for the stimulation of the macro-regions development to ensure its economic security is a relevant and priority task. The authors have analysed the intermediate results of some priority development areas since their creation in 2014. We have concluded that not enough time has passed to estimate whether this mechanism was effective or not in stimulating the regional growth and development of the business. Therefore, despite the traditional financial indicators of investment efficiency, we have included the estimation of quantitative change of one productive indicator depending on the change of a number of the parameters influencing this indicator in the assessment of the efficiency of priority development areas. We have estimated this quantitative change by means of the instruments of correlation and regression, and trend modelling. To apply this approach, we have designed a dependency model of the index of industrial production of Primorsky Krai as one of the indicators of the Economic Security Strategy on revealed factors, which cause the growth or decrease of this index. The economic interpretation of the model outputs consists in the following. When investments into fixed capital increase by 1 million rubbles, the index of industrial production in the region grows by 0,9 %. When the indicator of the real monetary income of the population increases by 1 thousand rubbles, the index of industrial production in the region decreases by 1,36 %. Trend forecasting has allowed to define such indicators as the investments into fixed capital and the real income of the population continue to change, the index of industrial production will show a steady downward trend for three next years. This proves that the policy of management of priority development areas in Primorsky Krai is inefficient. The research has concluded that from the perspective of ensuring the economic security of the macro-region, the creation of priority development areas in the Arctic will be effective only when all shortcomings of its functioning are eliminated. It is defined on the basis of the analysis of the corresponding experience of the Far East. High-quality forecasts will contribute to a positive impact from the creation of priority development area not only on the socio-economic sphere of the Arctic, but also on the strengthening the economic security of the macro-region in general. The results of the research can be used for the regional governance, monitoring of regional economic security, as well as for the increase in the scientific validity of state decisions.